Presence of the invasive land flatworm Platydemus manokwari (Platyhelminthes, Geoplanidae) in Guadeloupe, Martinique and Saint Martin (French West Indies) - Justine, Jean-Lou; Gey, Delphine; Vasseur, Julie; Thévenot, Jessica; Coulis, Mathieu; Winsor, Leigh (Zootaxa, 2021)
The land flatworm Platydemus manokwari (Platyhelminthes, Geoplanidae) is recorded from the islands of Guadeloupe, Martinique, and Saint Martin in the Caribbean arc. Photographs and records were obtained mainly from citizen science and ranged from the end of 2018 to February 2021; several specimens were deposited in the collections of the Muséum National d’Histoire Naturelle in Paris, France. Thirty records were from Guadeloupe, but only one from Martinique and from Saint Martin, respectively. The COI sequences of 3 specimens from Guadeloupe show that they belong to the World haplotype also found in many countries. We also report P. manokwari from Fort Myers, Florida, USA, with molecular characterization, which was also the World haplotype. This is the first published record of P. manokwari for Guadeloupe, Martinique and Saint Martin and the second for islands in the Caribbean, after Puerto Rico.